PERANCANGAN OTOMATISASI ABSENSI BERBASIS WEB DAN MOBILE MENGGUNAKAN METODE SDLC PADA PERUSAHAAN DODOL HARUM SARI - David Riyandi, Yandi; Nugraha, Yopi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The employee attendance recording process at Perusahaan Dodol Harum Sari currently faces operational constraints due to manual data management, leading to data vulnerability and calculation delays. This study aims to design a web and mobile-based employee attendance automation system using the SDLC method to enhance company administrative efficiency. The system development focuses on creating structured system designs based on operational requirements, which are then evaluated and validated together with company stakeholders to ensure alignment with operational needs. This research delivers a verified system design blueprint and user interface prototype tailored to minimize data recording errors and accelerate the administrative reporting process at Perusahaan Dodol Harum Sari.